FDG-PET/CT: novel method for viability assessment of livers perfused ex vivo. Issue 7 (18th March 2021) - Orita, Erika; Becker, Dustin; Mueller, Matteo; Hefti, Max; Schuler, Martin J.; Bautista Borrego, Lucia; Dutkowski, Philipp; Zeimpekis, Konstantinos; Treyer, Valerie; Kaufmann, Philipp A.; Eshmuminov, Dilmurodjon; Clavien, Pierre-Alain; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Purpose: Ex vivo liver machine perfusion is a promising option to rescue marginal liver grafts mitigating the donated organ shortage. Recently, a novel liver perfusion machine that can keep injured liver grafts alive for 1 week ex vivo was developed and reported in Nature Biotechnology . However, liver viability assessment ex vivo is an unsolved issue and the value of 18F-fluorodeoxyglucose (FDG)-PET/CT for such purpose was explored. Materials and methods: Discarded two human and six porcine liver grafts underwent FDG-PET/CT for viability assessment after 1 week of ex vivo perfusion. PET parameters [standardized uptake value (SUV)max, SUVmean, SUVpeak and total lesion glycolysis] were compared between hepatic lobes and between porcine and human livers. The prevalence of FDG-negative organ parts was recorded. The estimated effective radiation dose for PET/CT was calculated. Results: All organs were viable with essentially homogeneous FDG uptake. Of note, viability was preserved in contact areas disclosing the absence of pressure necrosis. Four porcine and two human organs had small superficial FDG-negative areas confirmed as biopsy sites. Total lesion glycolysis was significantly higher in the right hepatic lobe ( P = 0.012), while there was no significant difference of SUVmax, SUVmean and SUVpeak between hepatic lobes. There was no significant difference in FDG uptake parameters between porcine and human organs. The estimated effective radiation dose was 1.99 ± 1.67 mSv per organ. Conclusion: This study demonstrates the feasibility of FDG-PET/CT for viability assessment of ex vivo perfused liver grafts after 1 week.